NFVO standards and practice - Haining WANG; Huiling ZHAO (Dianxin kexue)
Network function virtualization (NFV) is an important trend in the development of future network,and is currently the work focus of the world's major standards organizations and open source communities.Network functions virtualization orchestrator (NFVO) is the core function of arranging and managing the NFV network and is the focus for operators and equipment manufacturers.The latest research progress of NFVO related international and domestic standards organizations and open source projects was expatiated,the NFVO system architecture and key components developed by Beijing Research Institute of China Telecom Co.,Ltd.and Jiangsu Branch of China Telecom Co.,Ltd.was expounded and NFVO's challenges in future R＆D and deployment was pointed out based on the existing practice of network.